Situation modeling of interaction between enterprises of the region and cross-border industrial clusters - Voronkova, А.; Zelenkina, К. (Національний університет "Львівська політехніка", 2013)
The article describes the background of development of the cluster forms of interaction between Ukrainian industrial enterprises; models of interaction of large and small businesses are considered, different situations of the "cluster and outsourcer" relationships are identified by weighted index of the interaction potential.
Keywords: enterprise; cross-border industrial cluster; situation modeling; region; interaction